Predicting Locust Invasions in Eastern India: Strategies and Awareness for Long-Term Control - S, Ghosh.; A, Roy. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Wind direction, a key factor in forecasting locust migration, indicates a potential desert locust invasion in eastern Indian states. Current control measures are in place, but we recommend additional vigilance regarding locust eggs. The rainfall from Super Cyclones like Amphan creates favourable breeding conditions for locusts. Additionally, these locusts may damage the Indian states again through reverse migration. To minimize damage, a long-term control policy extending until the Kharif season (June to October) is essential. Increasing farmer awareness and engaging local ecology groups can significantly enhance desert locust reporting and control efforts. By implementing a robust, multi-faceted strategy that includes long-term control policies, farmer education, and community engagement, we can mitigate the impact of desert locust invasions and protect the agricultural productivity and livelihoods of the affected regions.